Internet Use and Agricultural Household Food Insecurity in Indonesia - Dela Maria Ardianti; Djoni Hartono (Muhammadiyah University Press, 2022)
Food is an essential aspect of human life, but there are still households that experienced food insecurity. It caused a major challenge for policymakers to reduce food insecurity, especially at a household level. This study aims to analyze the association between internet use and food insecurity of agricultural households in Indonesia. This study uses the National Socio Economic Survey or Survei Sosial Ekonomi Nasional (Susenas) 2018 data. The food insecurity variable is measured by using the food insecurity experience scale (FIES) and internet use is a binary variable. Estimation of the impact of internet use on food insecurity uses Ordinary Least Square (OLS) regression. The result of this study indicates that internet use has a negative effect on agricultural household food insecurity. It means that internet use can reduce food insecurity in agricultural households. The policy implication directed to the government can improve the quality of internet infrastructure and improve content as positive information for the user, especially in the agricultural sector.